(untitled) (Fiep Bulletin - online, 2015)
This study, in process, has for objective to analyze the curriculum of the Leisure and Recreation discipline, in the ambit of the formation curriculum in physical education of the Parana State, seeking to capture the leisure concepts and recreation, as well as the teachers’ of the discipline pedagogic practices. This investigation is justified, considering that, great part of the curriculum in physical education in Brazil, still brings in your presuppositions the functional and utilitarian concept of the leisure, like the idea of the recreational pedagogic practice as mere reviews of plays and games. Besides, it is noticed that there is still, above all in the physical education courses a vision of the sense-common that considers the recreation as “child’s thing”, activities to soften the problems of the daily life, bread and circus, “animation” and other perceptions to respect. The used methodology is being verified through the investigation of qualitative character and, besides, of an empiric research that involves the combination among the documental research (analysis of the curriculum), of interviews and of the bibliographical research. The locus of the study is delimited for the courses of Degree of the Parana State Universities. The temporary results appear, except for rare exceptions, for the idea of the Recreation gone back to the consumption of recreational activities gone back to the practice of the plays and games, as well as camps, plays and other activities, seeking to subsidize the physical education classes starting from the understanding of specific classes of “recreation.” Besides, it is noticed in the curriculum, a strong tendency to the said practices “playful”, gone back to the market of the Industry of the Entertainment (hotels, birthday, parties, travels and others).